Gestational diabetes mellitus in mothers and long term cardiovascular disease in both parents: Results of over a decade follow-up of the Iranian population. (September 2019) - Kabootari, Maryam; Hasheminia, Mitra; Guity, Kamran; Ramezankhani, Azra; Azizi, Fereidoun; Hadaegh, Farzad
Abstract: Background and aims: We aimed at evaluating whether the presence of gestational diabetes mellitus (GDM) in mothers is associated with increased risk of incident cardiovascular disease (CVD) in both mothers and fathers. Methods: In this population-based study, 4308 Iranian women, aged 18–64 years, with at least 1 live-birth delivery, and free of CVD at baseline, were followed. Corresponding spouses were identified in 2547 cases. The association between history of GDM and incident CVD was assessed using multivariate Cox's proportional hazard in 3 models: model 1, unadjusted; model 2, adjusted for age, body mass index, smoking (for men), maternal parity, miscarriage, physical activity, hypertension and hypercholesterolemia, and model 3, further adjusted for diabetes mellitus. Results: After a median follow-up of 14.1 years, 314 mothers and 424 fathers experienced CVD. Women with history of GDM had an adjusted hazard ratio (HR), 95% CI of 1.85 (1.38–2.48) and 1.29 (0.96–1.75) for CVD in models 1 and 2, respectively. Furthermore, an independent association with CVD was observed in fathers with an adjusted HR of 1.35 (1.02–1.79) in the confounder adjusted model and even after further controlling for diabetes [1.36 (1.03–1.80)]. Moreover, all traditional risk factors, excluding BMI, showed an independent risk for CVD in both genders. Conclusions: Women with prior GDM showed an increased risk of CVD that was not independent of important CVD risk factors. However, among men, spousal history of GDM was an independent risk factor for incident CVD, even after considering important traditional risk factors, including diabetes. Graphical abstract: Image 1 Highlights: Women with prior GDM showed 85% higher risk of CVD in the unadjusted model. The risk of prior GDM among women was not independent of CVD risk factors. Fathers with spousal history of GDM had 36% higher risk of CVD. This association among fathers was independent of CVD risk factors (including diabetes).